Talkographics: Measuring TV and Brand Audience Demographics and Interests from User-Generated Content. Issue 3 (3rd July 2019) - Hill, Shawndra; Benton, Adrian; Panniello, Umberto
ABSTRACT: A wide variety of consumer data are available, including data that consumers make available online to the public for free. Because online users talk a lot about TV shows and brands online, these messages can be used to measure TV and brand audiences and help marketers answer questions about who is talking, what they are saying, and where to find them. However, the demographics of online users typically need to be inferred. We propose the use of "Talkographics, " which consists of combining publicly available text data from Twitter and data from the Facebook ads platform and the IMDb database in a novel way that enables group-level prediction of the demographics and interests of a large number of audiences. In addition, we demonstrate that group-level predictions can be used reliably in the context of building affinity networks and propose a recommender system using these Talkographic profiles.